Impact of the laser spatio-temporal shape on Breit–Wheeler pair production. (18th August 2021) - Mercuri-Baron, A; Grech, M; Niel, F; Grassi, A; Lobet, M; Di Piazza, A; Riconda, C
Abstract: The forthcoming generation of multi-petawatt lasers opens the way to abundant pair production by the nonlinear Breit–Wheeler process, i.e. the decay of a photon into an electron–positron pair inside an intense laser field. In this paper we explore the optimal conditions for Breit–Wheeler pair production in the head-on collision of a laser pulse with gamma photons. The role of the laser peak intensity versus the focal spot size and shape is examined keeping a constant laser energy to match experimental constraints. A simple model for the soft-shower case, where most pairs originate from the decay of the initial gamma photons, is derived. This approach provides us with a semi-analytical model for more complex situations involving either Gaussian or Laguerre–Gauss (LG) laser beams. We then explore the influence of the order of the LG beams on pair creation. Finally we obtain the result that, above a given threshold, a larger spot size (or a higher order in the case of LG laser beams) is more favorable than a higher peak intensity. Our results match very well with three-dimensional particle-in-cell simulations and can be used to guide upcoming experimental campaigns.